Balancing efficiency and clinical quality in dialysis centers: Insights from a nationwide DEA study in Taiwan - Shu-Chuan Jennifer Yeh; Wen Chun Wang; Andrew Pruett; Hsueh-Chih Chou (PLoS ONE, 2026)
Objectives The increasing prevalence of end-stage renal disease (ESRD), especially in aging populations, presents significant challenges for healthcare systems. Dialysis centers must navigate growing demands for cost efficiency while maintaining high-quality care. This study aimed to evaluate the relationship between operational efficiency and clinical quality in dialysis centers, using a systems-based performance assessment framework. Methods We analyzed 578 dialysis centers in Taiwan using Data Envelopment Analysis (DEA) to estimate operational efficiency. Clinical quality was assessed using outcome indicators including mortality rate, dialysis adequacy (urea reduction ratio [URR], Kt/V), serum albumin and hemoglobin levels, calcium-phosphate (Ca × P) product, and cardiothoracic ratio. Multiple regression analyses were conducted to examine associations between efficiency scores, clinical outcomes, and organizational characteristics, including chain affiliation and ownership type. Results Higher efficiency scores were significantly associated with lower URR, Kt/V, and Ca × P values, suggesting potential trade-offs between operational efficiency and clinical quality. Centers affiliated with chains generally reported better clinical outcomes. For-profit centers exhibited higher URR, Kt/V, and albumin levels, as well as lower Ca × P values, compared to their non-profit counterparts. Conclusions Operational efficiency in dialysis centers may come at the cost of certain clinical outcomes. However, organizational characteristics such as chain affiliation and for-profit ownership are linked to better quality indicators. These findings highlight the value of DEA as a tool for system-level performance evaluation and inform strategies to optimize dialysis care delivery.